Stakeholder perspectives regarding pragmatic clinical trial collateral findings - Stephanie R. Morain; Debra J. H. Mathews; Kevin Weinfurt; Elizabeth May; Juli M. Bollinger; Gail Geller; Jeremy Sugarman (Wiley, 2021)
Abstract Context Pragmatic clinical trials (PCTs), which are becoming widespread since they are relatively inexpensive and offer important benefits for healthcare decision‐making, can also present practical, ethical, and legal challenges. One such challenge involves managing "pragmatic clinical trial collateral findings" (PCT‐CFs), or information emerging in a PCT that is unrelated to the primary research question(s), yet may have implications for individual patients, clinicians, or health care systems from whom or within which data were collected. The expansion of PCTs makes it likely healthcare systems will increasingly encounter PCT‐CFs, yet little guidance exists regarding their appropriate management. Methods We conducted semi‐structured interviews with key stakeholders experienced in the conduct or oversight of PCTs and those in health system leadership. Interviews explored respondents' experience with PCTs and PCT‐CFs, and actual or hypothetical reactions to PCT‐CF management. We used standard methods of qualitative analysis to identify key themes. Findings Forty‐one stakeholders participated. Four key themes emerged. First, discussions of PCT‐CFs are complicated by layers of ambiguity related to both the nature of PCTs themselves, and unanticipated results that emanate from them. Second, management of PCT‐CFs is context‐specific, and not amenable to a "one‐size‐fits‐all" approach. Third, there was a wide diversity of attitudes regarding the scope of researcher responsibilities in PCTs. Fourth, PCT‐CFs had generally not been previously considered by respondents, but there was widespread belief in the importance of prospective planning to anticipate such issues in future PCTs. Conclusions PCT‐CFs are likely to increase, yet those charged with PCT‐CF decision‐making and their disclosure are unlikely to have experience with these issues. Further deliberation about the ethical obligations and implementation processes regarding PCT‐CFs is needed. To enhance the likelihood of developing sound policies and practices, such deliberations should include the input and perspectives of key stakeholders in PCTs, including professionals, policy makers, and patients.